PARENTS KNOWLEDGE OF CASES OF PERSISTENCY IN A CHILD TEETH: PENGETAHUAN ORANG TUA MURIDTERHADAP KASUS PERSISTENSI PADA GIGI ANAK (Jurnal Kesehatan Siliwangi, 2020)
Parents knowledge are very important in the formation underlying behaviours that support the oral hygiene of children. Teeth are very important in children’s growth and development. The primary school children is a transition phase from primary teeth to permanent teeth which is regarded as susceptible to oral disease specially persistency of teeth. The purpose of this research is to obtain data on the parents knowledge of the case of persistency in children teeth. The method of study uses literature studies, by reviewing and analyzing from written material or based on its context. After reviewing the literature results, the parental knowledge off all three sources shows good results about the knowledge of the number and type of teeth, and enough about teeth persistency, and less about teeth growth. So it can be concluded that the knowledge of parents about teeth growth is still relatively low